Drying equipment for dried fruit processing - HONG QINGMEI; DUAN JIHUA (2022)
The utility model belongs to the technical field of dried fruit processing, and particularly relates to drying equipment for dried fruit processing, which comprises a box body, the box body is provided with a rear air duct and a side air duct, the rear air duct is provided with a fan assembly, the side air duct is provided with an air outlet, the box body is provided with a placing mechanism, and the side air duct is provided with a heating assembly. The placing mechanism comprises a rotating shaft and a placing plate, the rotating shaft is connected with the box body, the placing plate is connected with the rotating shaft, the placing plate is provided with an annular baffle, and the annular baffle is provided with a through hole; the rotating shaft is connected with a driving assembly. A box door is hinged to the box body. According to the fruit slice drying device, the driving assembly drives the two rotating shafts to rotate, and the rotating shafts rotate to drive the placing plates to rotate, so that fr